A Language Modelling Tool for Statistical NLP - Pereira, Daniel Bastos; Paraboni, Ivandré (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL), 2007)
In recent years the use of statistical language models (SLMs) has become widespread in most NLP fields. In this work we introduce jNina, a basic language modelling tool to aid the development of Machine Translation systems and many other text-generating applications. The tool allows for the quick comparison of multiple text outputs (e.g., alternative translations of a single source) based on a given SLM, and enables the user to build and evaluate her own SLMs from any corpora provided.